Malay Version of the Fear of COVID-19 Scale: Validity and Reliability - Nicholas Pang Tze Ping; Assis Kamu; Nurfarah Lydia Binti Hambali; Ho, Chong Mun; Mohd Amiruddin Kassim; Noor Hassline Mohamed; Friska Ayu; Syed Sharizman Syed Abdul Rahim; Azizan Omar; Saffree Mohammad Jeffree (2020)
The newly developed Persian Fear of COVID-19 Scale (FCV-19S) is a seven-item unidimensional scale that assesses the severity of fear of COVID-19. A translation and validation of the FCV-19S in the Malay language was expedited due to the severe psychological sequelae of COVID-19 in Malaysia. Formal WHO forward and backward translation sequences were employed in translating the English version into Malay. Malaysian university participants were recruited via convenience sampling online using snowball methods. The reliability and validity properties of the Malay FCV-19S were rigorously psychometrically evaluated (utilising both confirmatory factor analysis and Rasch analysis) in relation to socio-demographic variables and response to the depression, anxiety and stress subscales of the Malay validation of the DASS-21. The sample comprised 228 Malaysian participants. The Cronbach α value for the Malay FCV-19S was 0.893 indicating very good internal reliability. The results of the confirmatory factor analysis showed that the uni-dimensional factor structure of the FCV19S fitted well with the data. The FCV-19S-M was significantly correlated with anxiety (r = 0.481, p < 0.001) and stress (r = 0.389, p < 0.001) subscales of DASS-21. The FCV-19S-M’s properties tested using Rasch analysis were also satisfactory. Hence, the Malay FCV-19S is valid and reliable, with robust psychometric properties from classical and modern psychometric methods. It therefore is a highly crucial and timely addition to the psychological toolkit both in operational and research settings in identifying, managing and responding to the psychological distress engendered by COVID-19.